(untitled) (Colombia Medica, 2018)
The creator of several vaccines given to children around the world everyday, Maurice Hilleman, advised that at the same time that new vaccines would emerge in the 21st century due to technological advances, unfounded criticisms of vaccines would extended beyond spurious belief systems to actual anti-vaccine movements. He pointed out that these movements are aimed at disruption of vaccine programmes through use of public media including the press, television and the Internet in his response to the spurious association between autism and Crohn’s disease with one of his main creations, MMR vaccine (1). Andrew Wakefield, author of an unsound scientific paper in 1998 proposing such association, was motivated by an undue agreement to support a lawsuit (2). Nevertheless, Wakefield remains as an outstanding voice in the anti-vaccine movement (3). Why the once feared diseases disappeared from collective memory? On the other hand, adverse events following immunization that we used to bear as a fair risk for the expected benefit are not accepted anymore? Why we have forgotten the benefits, but not forgiven the risks? How could we define new strategies to face the challenges of immunization programmes? The 1976 swine flu immunization programme in United States was a landmark on the questioning of risk-benefit ratio for vaccines. The concern on a new pandemic flu after triggered a large mass vaccination campaign. Pandemic flu cases did not appear, but serious adverse events did raise questions on public opinion (4). This contrasted with most of the vaccines where decreasing incidence of a preventable diseases compared with safety concerns seems to be acceptable for the society. On the other hand, efficacious vaccines, like whole-cell pertussis vaccine (wP), have been also on the spot due to relevant adverse events after immunization...